Profiles Associated with Sarcopenia in Hepatoma Patients Underwent Transcatheter Arterial Chemoembolization: A Data‐Mining Analysis. Issue 2 (1st July 2018) - Hirota, Keisuke; Kawaguchi, Takumi; Hashida, Ryuki; Koya, Shunji; Bekki, Masafumi; Goshima, Norihiro; Yoshiyama, Teruhito; Otsuka, Takashi; Nozoe, Ryosuke; Nakano, Dan; Shirono, Tomotake; Shimose, Shigeo; et al.
Abstract: Aims: Sarcopenia is a prognostic factor in patients with hepatocellular carcinoma (HCC). Transcatheter arterial chemoembolization (TACE) may aggravate sarcopenia because of post‐embolization syndrome. The aims of this study are to investigate changes in skeletal muscle mass after TACE and its risk profiles in patients with HCC. Methods and results: We enrolled 104 HCC patients (age 73.5 [41.0–88.0] years, female/male 35/69, body mass index 22.4 [16.0–32.7]). Changes in skeletal muscle mass were evaluated by Δskeletal muscle index (SMI) using computed tomography before and after TACE. Factors correlated with ΔSMI were evaluated. Independent factors and profiles associated with a decrease in SMI were evaluated by multivariate analysis and decision‐tree analysis, respectively. SMI was significantly decreased after TACE in patients with HCC (32.8 vs. 30.6 cm 2 /m 2 ; P=0.0001). However, there was no significant correlation between the ΔSMI and other variables including Δalbumin. In the logistic regression analysis, no factor was significantly associated with a decrease in SMI. In the decision‐tree analysis, sex was selected as the initial split and, in female, 74% of subjects showed a decrease in SMI. While, in male, an estimated glomerular filtration rate (eGFR) ≤81.7 ml/min/1.73 m 2 was the second split; of these patients, 74% of subjects had a decreased SMI. Conclusions: We demonstrated that skeletal muscle mass was decreased after TACE in patients with HCC. "female" and "male who had a lower eGFR" were profile for a decrease in skeletal muscle mass. Thus, such patients who have HCC treated with TACE may benefit from preventive treatment for sarcopenia.